An introduction to early Judaism - VanderKam, James C. (Grand Rapids, MI William B Eerdmans Publishing Company, 2001)
This handbook is an introduction to early Judaism, including its history, literature, and religious institutions. It will be useful to every student or scholar who is interested in this period.
The time of the second temple. The Persian period (538-332 BCE) ; The Hellenistic age (332-63 BCE) ; The Roman period (63 BCE and beyond) -- Jewish literature on the Second Temple period. Second Temple texts in the Hebrew Bible ; The classification of Second Temple literature ; Jewish writings of the Second Temple period -- Synthesis : leaders, groups, and institutions. Rulers and leaders ; Groups ; Worship ; Scriptures.
Includes bibliographical references (pages 219-223) and index.
Keywords: Bible. -- Criticism, interpretation, etc; Jews -- History -- 586 B.C.-70 A.D.; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Apocryphal books (Old Testament) -- Criticism, interpretation, etc